1978
DOI: 10.1002/jbm.820120308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sunlight stability of polyurethane elastomers for maxillofacial use. I

Abstract: The evaluation of the efficiency of polymer additives with special emphasis on uv absorbers and antioxidants in polyurethane elastomers has been completed. Aliphatic polyurethanes were chosen for this study because their properties closely relate to the requirements of maxillofacial prosthesis. The polyurethane elastomers were either synthesized by ourselves or formulated according to the manufacturer's recommendation. Eleven different types of uv absorbes, coupled with one antioxidant, were incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…[81415161718] UV stabilizers have been used extensively in the polymer, paint, cosmetic, and plastic industries as well as for wood and cellulose fabrics to prevent color degradation and increase the life of the products. [192021]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[81415161718] UV stabilizers have been used extensively in the polymer, paint, cosmetic, and plastic industries as well as for wood and cellulose fabrics to prevent color degradation and increase the life of the products. [192021]…”
Section: Discussionmentioning
confidence: 99%
“…Chu and Fischer[17] used 1.5% weight UVA and found that it was effective in reducing yellowing of the elastomer, Lemon et al . [8] used 12%, 25% by weight UVA and found that these did not protect the samples and Tran et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10]24 The strategies for stabilization of elastomers have included the use of UV stabilizers, thermochromic pigments and opacifiers. 7,[13][14][15][16][17] Such attempts at stabilization of elastomers have yielded mixed results. Kantola 14 found that thermochromic pigments were very sensitive to UV radiation and not suitable for prosthetic application whereas Kiat-amnuay 13 studied various concentrations of opacifiers and found that they prevent colour degradation overtime.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, varying concentrations of UV stabilizers have been documented by researchers with mixed results (Chu and Fischer et al 16 used 1.5% weight UVA and found that it was effective in reducing yellowing of the elastomer, Lemon et al 7 used 12%, .25% by weight UVA and found that these did not protect the samples and Tran et al 15 used 75% by weight UVA and HALS and found that this was effective only for a certain pigmented groups). In this study 1% by weight of UVA (Chimassorb 81) and 1% by weight of HALS (Uvinul 5050) for Groups B and C respectively and 0.5% of each for Group D was used.…”
Section: Discussionmentioning
confidence: 99%